An evaluation of the marketing and distribution channels of the Mzuzu Coffee Planters Cooperative Union (MZCPCU) - Jussa, Leman Abdulrazak Wyson (Rhodes University, Faculty of Commerce, Rhodes Business School, 2011)
Literature and the cooperative movement in Malawi shows that the first cooperative was established in 1947. Since the economy of the country depends on agriculture, most cooperatives were strongly developed in the fields of agricultural production, and processing and marketing. The first coffee cooperative was registered in 1950, known as the Nchenachena Coffee Producers Cooperative Society. After Malawi 's independence in 1964, agricultural cooperatives were dissolved and government formed the Farmers Marketing Board (FMB) to take over all marketing activities of all crops, including coffee. The FMB was replaced by the Agricultural Development and Marketing Corporation (ADMARC) in 1967. After the dissolution of agricultural cooperatives, government saw the need for crop development and established Smallholder Coffee Authority in 1971. The Smallholder Coffee Authority worked up to 1999 when it collapsed because of administrative and financial problems. Due to the failure of the Smallholder Coffee Authority, the government of Malawi reintroduced agricultural cooperatives in 1999. Mzuzu Coffee Planters ' Cooperative Union was formed in 2006 following the re-introduction of cooperatives. The union is mandated to promote sustainable production, processing and marketing of Arabica coffee on behalf of the farmers. Since its inception, the output of coffee for export from the Mzuzu Coffee Planters Cooperative Union has increased from 156 tonnes in 2006 to over 400 tonnes in 2009. The increase in coffee exports was not by mere chance but a number of factors contributed to this success. The main reasons for this success were: "¢ Strong prior relationship between the growers and the buyers "¢ The uniqueness of the cooperative business model "¢ The unique taste and quality of coffee grown "¢ The introduction of a different approach to farming coffee Currently there is high demand for organic coffee and this could be a niche market that is not only rewarded with premium prices but also creates environmental friendly business. The union considers Fair Trade market as an alternative approach to conventional trade, aiming at improving the livelihoods of smallholder producers by improving payments, giving them fair prices and providing continuity in trading relationships.
Keywords: Mzuzu Coffee Planters Cooperative Union; Coffee -- Marketing -- Malawi; Marketing channels -- Evaluation -- Malawi; Agricultural development projects -- Malawi